Ensuring the functional stability of the information system of the power plant on the basis of monitoring the parameters of the working condition of computer devices - Barabash, Oleg; Svynchuk, Olha; Salanda, Ivanna; Mashkov, Viktor; Myroniuk, Mykola (Національний технічний університет "Харківський політехнічний інститут", 2024)
The functional stability of the information system of the power plant is ensured by a complex of processes and mechanisms that are capable of maintaining the normal operation of the system even in the event of errors, failures or negative impacts. The aim of the research. An important aspect of ensuring the functional stability of an information system is the monitoring of its healthy state, as it helps to identify, analyze and respond to any problems in a timely manner, ensuring the reliable and uninterrupted operation of the system. It was decided to choose a test diagnosis based on the principle of a wandering diagnostic core. Research results. An algorithm for detecting failures in the system has been developed based on the decryption of the totality of the results of the system's test checks. The developed software application allows you to monitor the state of various components of the information system and detect possible problems or failures in a timely manner in order to support the continuous operation of the system. This application allows you to increase the reliability of diagnostics, reduce the time of diagnostics, and carry out diagnostics with the specified completeness and depth. The depth and completeness of diagnosis is determined by the test task. Verification. To confirm the correctness of the developed software product, mathematical modeling of the process of diagnosing the information system, which was divided into several subsystems containing a certain number of modules, was carried out. For the division into subsystems, the number of modules in each subsystem is important -it should not exceed 30 modules. This limitation is due to the limited computing power of modern microprocessor technology during the solution of a class of NP-complete problems.

Функціональна стійкість інформаційної системи електростанції забезпечується комплексом процесів та механізмів, які здатні підтримувати нормальну роботу системи навіть в умовах виникнення помилок, відмов або негативних впливів. Мета дослідження. Важливим аспектом забезпечення функціональної стійкості інформаційної системи є моніторинг її справного стану, оскільки він допомагає ідентифікувати, аналізувати та вчасно реагувати на будь-які проблеми, забезпечуючи надійну та безперебійну роботу системи. Було прийнято рішення обрати тестове діагностування за принципом блукаючого діагностичного ядра. Результати дослідження. Розроблено алгоритм виявлення відмов в системі на основі дешифрації сукупності результатів тестових перевірок системи. Розроблений програмний застосунок дозволяє відстежувати стан різних компонентів інформаційної системи та своєчасно виявляти можливі проблеми або відмови з метою підтримки безперервної роботи системи. Даний застосунок дозволяє підвищити достовірність діагностування, знизити час діагностування та проводити діагностування із заданою повнотою та глибиною. Глибина і повнота діагностування визначаються тестовим завдання. Верифікація. Для підтвердження правильності розробленого програмного продукту проведено математичне моделювання процесу діагностування інформаційної системи, яка розбивалась на кілька підсистем, які містять в собі певне число модулів. Для розбиття на підсистеми важливе значення має кількість модулів у кожній підсистемі –вона не повинна перевищувати 30 модулів. Дане обмеження обумовлено обмеженістю обчислювальної потужності сучасної мікропроцесорної техніки під час рішення класу NP-повних задач.
Забезпечення функціональної стійкості інформаційної системи електростанції на основі моніторингу параметрів справного стану обчислювальних пристроїв
Keywords: destabilizing factors; diagnostics; test control; probability; limited computing power; modern microprocessor technology; інформаційна система; функціональна стійкість; дестабілізуючі фактори; діагностування; тестовий контроль